How Finland Survived Stalin From Winter War to Cold War, 1939-1950 - Rentola, Kimmo 1953- (Yale University Press, 2024)
A dramatic and timely account of Stalin's failed invasion of Finland in 1939, and the decade of wars and fraught relations that followed.